Blinding and sham control methods in trials of physical, psychological, and self-management interventions for pain (article I): a systematic review and description of methods - Hohenschurz-Schmidt, David; Draper-Rodi, Jerry; Vase, Lene; Scott, Whitney; McGregor, Alison; Soliman, Nadia; MacMillan, Andrew; Olivier, Axel; Cherian, Cybill Ann; Corcoran, Daniel; Abbey, Hilary; Freigang, Sascha; et al. (Pain, 2023)
Blinding is challenging in randomised controlled trials of physical, psychological, and self-management therapies for pain, mainly because of their complex and participatory nature. To develop standards for the design, implementation, and reporting of control interventions in efficacy and mechanistic trials, a systematic overview of currently used sham interventions and other blinding methods was required. Twelve databases were searched for placebo or sham-controlled randomised clinical trials of physical, psychological, and self-management treatments in a clinical pain population. Screening and data extraction were performed in duplicate, and trial features, description of control methods, and their similarity to the active intervention under investigation were extracted (protocol registration ID: CRD42020206590). The review included 198 unique control interventions, published between 2008 and December 2021. Most trials studied people with chronic pain, and more than half were manual therapy trials. The described control interventions ranged from clearly modelled based on the active treatment to largely dissimilar control interventions. Similarity between control and active interventions was more frequent for certain aspects (eg, duration and frequency of treatments) than others (eg, physical treatment procedures and patient sensory experiences). We also provide an overview of additional, potentially useful methods to enhance blinding, as well as the reporting of processes involved in developing control interventions. A comprehensive picture of prevalent blinding methods is provided, including a detailed assessment of the resemblance between active and control interventions. These findings can inform future developments of control interventions in efficacy and mechanistic trials and best-practice recommendations.
Online veröffentlicht: 11. Juli 2022
Gesehen am 25.05.2023